Faktor-Faktor yang Berhubungan dengan Kesehatan Reproduksi Remaja di SMPN 3 Pantai Raja Wilayah Kerja UPT Puskesmas Pantai Raja Kabupaten Kampar - Delvita Delvita; Aifa, Wira Ekdeni; Tanberika, Fajar Sari; Rizka Mardiya (Pusat riset dan Inovasi Nasional, 2026)
Adolescence has problems, one of which is reproductive health. Factors that influence reproductive health include socioeconomic and demographic factors, cultural and environmental factors, psychological factors, and biological factors. This study aims to determine the factors related to the reproductive health of adolescents at SMPN 3 Pantai Raja, the working area of the UPT Pantai Raja Health Center (respondent characteristics, parental characteristics, adolescent knowledge, family support). This type of research is descriptive with a cross- sectional approach. The population is all seventh grade students at SMPN 3 Pantai Raja, the working area of the UPT Pantai Raja Health Center, grade VII in October 2025 with a sample of 59 people using total sampling. Data analysis uses descriptive data analysis and statistic chi square, namely explaining data about each variable. The results of the study showed that all (100%) were in the 35-49 age group, the majority (57.6%) had secondary education, the majority (59.3%) were employed, the majority (71.1%) had sufficient support, all (100%) were aged 11-14 years, almost all (81.4%) were female, and the majority (57.6%) had sufficient knowledge. The conclusion of this research is that there is a relationship between knowledge and support from parents of class VII students with a p-value of 0.001 and factors related to adolescent reproductive health influence each other to influence reproductive health during adolescence. Therefore, it is hoped that community health centers will increase knowledge and understanding, especially in providing services to adolescents, to provide more information about adolescent reproductive health.